La telenovela brasileña: de gata cenicienta a reina mediática - Jose Marques de Melo (Estudios sobre las Culturas Contemporáneas)
Analysis of the coverage done by the printed media on "telenovelas" (Latin American soap operas), popular programmes daily released by television networks in Brazil. The results confirm the hypothesis of the social legitimation of this format of the TV fictional genre, early rejected by the cultural elites in the country. Through strategies of agendasetting the cultural industries gained recognition of the prestige papers and stimulated the participation of TV fans in the debate of public issues.